ANALISIS PENGARUH PROMOTION DAN E-TRUST TERHADAP ELOYALTY DENGAN E-SATISFACTION SEBAGAI VARIABEL INTERVENING - Gemilang,, Izhhar; Soesanto, Harry (Faculty of Economics and Business Diponegoro University, 2021)
The Development of technology and information has developed very rapidly, making it easier for people to obtain information to meet their needs. One of them is through online buying and selling (e-commerce). Bukalapak is one of the largest e-commerce sites but has experienced a decline in visitor growth compared to its competitors, it is important to maintain existing user loyalty. This study aims to analyze the effect of e-trust and promotion on e-loyalty with e-satisfaction as an intervening variable. The Population used in this study were Diponegoro University FEB students who are users of the Bukalapak e-commerce site and have made transactions at least once in the past 1 year. The number of samples used in this study were 110 respondents. The data collection method was carried out through questionnaires that were distributed online due to the pandemic that was hitting the world. This study used Structural Equation Modeling (SEM) analysis techniques with AMOS analysis tools. The Results of this study indicate that promotion has a positive and significant effect on e-satisfaction, e-trust has a positive and significant effect on e-satisfaction and esatisfaction has a positive and significant effect on e-loyalty. Apart from that, e-trust also have a positive and significant direct effect on e-loyalty.